Indigenous knowledge of bamboos by Naga community, Tasikmalaya District, West Java, Indonesia - BUDI IRAWAN; RUHYAT PARTASASMITA; NGESTI RAHAYU; TIA SETIAWATI; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Irawan B, Partasasmita R, Rahayu N, Setiawati T, Iskandar J. 2019. Indigenous knowledge of bamboos by Naga community, Tasikmalaya District, West Java, Indonesia. Biodiversitas 20: 1423-1434. Naga community is recognized as one of Sundanese traditional groups who reside in Neglasari village, Salawu Subdistrict, Tasikmalaya District, West Java Province, Indonesia. This community has been holding firm customs and culture. For daily needs, they take advantage of plant diversity around their homes, including bamboo. The aim of this study was to investigate the diversity (species and variations/landraces), utilization and management of bamboo among Naga community. The method used in this study was mixed method by combining qualitative and quantitative data collection with ethnobotany approach used in ethnobotanical studies. Semi-structured or deep interview, structured interviews, and participant observation method were used to collect data in the field. The result of study showed that there were 7 species and landraces of bamboos, namely Bambusa vulgaris Schard ex Wendl. var. vulgaris (haur hejo), Bambusa vulgaris Schard ex Wendl. var. striata (Lodd. ex Lindley) Gamble (haur koneng), Gigantochloa apus (J.A. & J.H. Schult) Kurz. (awi tali), Gigantochloa pseudoarundinacea (Steud) Widjaja (awi gede/awi gombong), Gigantochloa atter (Hassk) Kurz. (awi temen), Gigantochloa atroviolacea Widjaja (awi hideung) and Schizostachyum iraten Steud (awi tamiyang) were documented and used in the gardens of Naga communities. Bamboos are traditionally used as building materials, woven for container, traditional musical instruments, equipment for cooking, agricultural and livestock tools, foodstuffs, and others. Bamboo plants in the garden have been traditionally managed which consists of land preparation, planting, maintenance, pest control, harvesting, and utilization. The conservation of bamboos has been traditionally done by Naga community, including selective cutting of bamboo trees instead of clear-cutting, and keeping the bamboos garden not being converted to other land uses.